2003
DOI: 10.1094/pdis.2003.87.8.929
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Virulence Phenotypes of Heterodera glycines in Missouri

Abstract: The soybean cyst nematode, Heterodera glycines, is the most economically important pathogen of soybean in Missouri. Knowledge of the nematode's distribution and ability to adapt to resistant varieties is important for determining crop losses and establishing research priorities. No previous surveys of Missouri have provided reliable population density and phenotypic diversity data; therefore, we conducted a random survey to obtain both. Two samples from each of 200 fields were collected; 392 samples were proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
76
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(79 citation statements)
references
References 8 publications
2
76
0
1
Order By: Relevance
“…The SCN (Heterodera glycines 'Ichinohe') inbred populations PA3 and TN19 were obtained from a publicly available collection at the University of Illinois at Urbana-Champaign and mass selected according to standard procedures (Niblack et al, 1993) on soybean cv Williams 82 and PI 437654, respectively. HG type tests (Niblack et al, 2002) confirmed that the PA3 population was HG type 0 and the TN19 population was HG type 1-7.…”
Section: Plant and Nematode Materialsmentioning
confidence: 99%
“…The SCN (Heterodera glycines 'Ichinohe') inbred populations PA3 and TN19 were obtained from a publicly available collection at the University of Illinois at Urbana-Champaign and mass selected according to standard procedures (Niblack et al, 1993) on soybean cv Williams 82 and PI 437654, respectively. HG type tests (Niblack et al, 2002) confirmed that the PA3 population was HG type 0 and the TN19 population was HG type 1-7.…”
Section: Plant and Nematode Materialsmentioning
confidence: 99%
“…A collection of SCN inbred lines (selected by single cyst descent (half-sib matting) for over 30 generations) is maintained at 27°C in a greenhouse facility on appropriate host plants using plastic crocks as described by (Niblack 1993). TN10 was selected on tomato (cultivar Tiny Tim) and TN20 was selected on the SCN resistant soybean cultivar Hartwig.…”
Section: Nematode Inbred Line Culture and Characteristicsmentioning
confidence: 99%
“…Com bases nessas informações, sistemas de previsão poderão ser desenvolvidos e estratégias de controle, principalmente o uso de variedades resistentes, podem ser otimizadas. Em regiões onde há alta DI, deverão ser recomendadas variedades mais resistentes; à semelhança do que ocorre para nematóide dos cistos da soja nos Estados Unidos (Niblack et al, 1993).…”
Section: Resultsunclassified